2008
DOI: 10.1210/en.2008-1210
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Various Selective Estrogen Receptor Modulators with or without Conjugated Estrogens on Mouse Mammary Gland

Abstract: Selective estrogen receptor modulators (SERMs) are small molecules that, depending on the end point measured, may either function as estrogen receptor (ER) agonists or antagonize estrogens' agonist activity. A key feature of SERMs is the inhibition of ER agonist action on the uterus and mammary gland, but the degree of antagonism varies among compounds and end points. Bazedoxifene is a SERM that is being clinically evaluated both as a monotherapy for the prevention and treatment of osteoporosis and in combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
89
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 26 publications
1
89
0
3
Order By: Relevance
“…Preclinical data have suggested that the combination treatment of bazedoxifene and conjugated estrogens (CE) might lead to a more favorable benefit-risk profile in the treatment of menopause symptoms, including favorable vasomotor, lipid, and skeletal response with minimal stimulation in the uterus (Kharode et al, 2008;Peano et al, 2009). This combination therapy also shows efficacy in the treatment of osteoporosis in a manner that prevents uterine growth, with decreased uterine wet weight and lower cholesterol levels .…”
Section: Nuclear Receptors and Their Selective Modulatorsmentioning
confidence: 99%
“…Preclinical data have suggested that the combination treatment of bazedoxifene and conjugated estrogens (CE) might lead to a more favorable benefit-risk profile in the treatment of menopause symptoms, including favorable vasomotor, lipid, and skeletal response with minimal stimulation in the uterus (Kharode et al, 2008;Peano et al, 2009). This combination therapy also shows efficacy in the treatment of osteoporosis in a manner that prevents uterine growth, with decreased uterine wet weight and lower cholesterol levels .…”
Section: Nuclear Receptors and Their Selective Modulatorsmentioning
confidence: 99%
“…Moreover, there was no influence of bazedoxifene on the overgrowth of endometrium or myometrium. In the studies comparing the effect of bazedoxifene, raloxifene, and lasofoxifene on the breasts of the mice, the first medicine showed the lowest stimulation and turned out to be the most effective antagonist of influence of conjugated estrogens on the breast, which was confirmed by histopathological tests [17].…”
Section: Selective Estrogen Receptor Modulatorsmentioning
confidence: 83%
“…Dodatkowo wykazano brak wpływu stosowania bazedoxifenu na przerost nabłonka śluzówki macicy i myometrium. W badaniach porównujących wpływ bazedoxifenu, raloxyfenu i lasoxifenu na gruczoł piersiowy myszy, ten pierwszy wykazał najsłabszą stymulację i okazał się najbardziej efektywnym antagonistą wpływu skoniugowanych estrogenów na gruczoł piersiowy, co potwierdziły badania histopatologiczne [17].…”
Section: Selective Estrogen Receptor Modulatorsunclassified
“…(Stovall & Pinkerton, 2008) Preclinical studies have shown that bazedoxifene antagonizes estrogen-induced uterine and mammary gland stimulation more effectively than other SERMs like raloxifene and lasofoxifene. (Peano et al, 2009;Kharode et al, 2008) A randomized, double-blind, placebocontrolled Phase III trial in 3,397 postmenopausal women examined the effect of bazedoxifene 10, 20, or 40 mg combined with conjugated estrogens 0.625 mg or 0.45 mg on bone and endometrium. In this trial, the bazedoxifene plus conjugated estrogen combination therapy showed a statistically significant increase in BMD and a decrease in bone biochemical turnover markers compared with placebo.…”
Section: Bazedoxifene and Conjugated Estrogen Combination Therapymentioning
confidence: 99%